Christians are hate-filled hypocrites-- and other lies you've been told : a sociologist shatters myths from the secular and christian media - Wright, Bradley R. Entner (Minneapolis, Minn. : Bethany House, 2010)
"A research sociologist uses statistics to reveal the state of the Evangelical Church, showing that the church is in better shape than the secular and Christian media claims"--Provided by publisher.
Why do we hear so much bad news about Christianity? -- Is American Christianity on the brink of extinction? -- Are we losing our young people? What will happen in the future? -- Are evangelicals all poor, uneducated, southern whites? -- Do Christians think and do Christian things? -- Have Christians gone wild? -- Do Christians love others? -- What do non-christians think of us? -- What do we make of it all? -- Afterword -- Appendix 1: identifying evangelical Christians -- Appendix 2: data sets -- Appendix 3: bivariate vs. multivariate analysis -- Appendix 4: statistical significance.
Includes bibliographical references (p. [245]-249).
Keywords: Evangelicalism -- United States; Christianity -- United States; Christianity -- Controversial literature; Mass media in religion -- United States